Post-industrial 2.0 – Social Web as the second coming of the post-industrial society - Kupias, Anton (My University, 2012)
This study presents a review of theories of the so-called post-industrial society, and proposes that the concept of post-industrial society can be used to understand the recent developments of the World Wide Web, often described as Web 2.0 or social Web. The study combines theories ranging from post-war management science and cultural studies to software development, and tries to build a holistic view of the development of the post-industrial society, and especially the Internet. The discourse on the emergence of a post-industrial society after the World Wars has addressed the ways in which the growing importance of information, and innovations in digital communications technology, are changing our society. It is furthermore deeply connected with the discourse on the postmodern society, which emphasizes cultural fragmentation, intertextuality, and pluralism. The Internet age is characterized by increasing masses of information that are managed through various technologies. While 1990s Internet technologies often used the network as a traditional broadcasting channel with added interactivity, Web 2.0 technologies are specifically designed to utilize the network model by facilitating communication between various services and devices, and analyzing the relationships between users and objects in order to produce intelligent insight. The wide adoption of the Internet, and recently of Internet-enabled mobile devices, is furthermore continuously producing new ways of communicating, consuming, and producing. Applications of the social Web, such as social media or social networking services, are permanently changing our traditional social, cultural, and economic practices. The study first presents an overview of the post-industrial society, the Internet, and the concept of Web 2.0. Then the concept of social Web is described with an analysis of the term social media, the brief histories of the interactive Web and social networking services, and a description of the concept ―long tail‖, used to represent the masses of information available in the Web that do not receive mainstream attention. Finally, methods for retrieving and filtering information, modeling social and cultural relationships, and communicating with customers, are presented.